Effect of fatigue on running kinetic asymmetry in noncontinuous & continuous constant speed protocol - Ali, M. H.; Hiang, H. K.; Gerald, S.; Balasekaran, G. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
Kinetic asymmetries in running gait are well studied but their interaction with muscular fatigue, perceived exertion and/or metabolic stress, need further attention to understand and report limb laterality with fatigue progression during a non-continuous & a continuous constant speed protocols. For study, 13 young male runner's data for kinetic asymmetry (KA), stride rate (SR), blood lactate (BLa), muscular fatigue (RPEM) and overall body feel (RPEo) were collected. Kendall's tau-b reported a non-significant correlation between KA, SR and RPEM and a significant correlation between BLa, RPEo and RPEM whereas Tuckey post hoc test revealed non-significant effect of RPEM on KA and SR in both tests. Findings suggest that, observed KA with fatigue progression may be subject to inter-individual coordinated motor control based on overall running physiological state of body as there has no direct correlation been found with BLa, RPEM and RPEo in this study.